KAJIAN FRAKSI METANOL DARI EKSTRAK METILEN DIKLORIDA KULIT KAYU BATANG PELAWAN (Tristania whitiana Griff.) SEBAGAI ANTIBAKTERI - Purwantiningsih Sugita (Molekul, 2007)
Antibacterial compound from methanol fraction of methylene dichloride extract of pelawan bark had been studied. Pelawan bark was extracted using ethanol 95% and CH2Cl2-water (1:1), respectively. Extract of CH2Cl2 was partitioned using hexane-methanol 90% (1:1). Afterwards, methanol fraction was analyzed by thin layer chromatography methods to find the best eluent for column chromatography. The best eluent came from mixture of acetone-chloroform-methanol (0,6:4:0,4). The fractionation yielded 16 fractions with the first (M1) and the third (M5) fractions became the one spotted fractions. M1 and M5 fractions were examined for their antibacterial activity using paper diffusion methods by determining minimum inhibitory concentration value. M1 fraction showed greater activity than M5 fraction with minimum inhibitory concentration value of 2,7857 mg/mL. The result of phytochemistry test showed that both fractions contain terpenoid.